A Robust and Broadly Applicable Cobalt‐Catalyzed Cross‐Coupling of Functionalized Bench‐Stable Organozinc Pivalates with Unsaturated Halides. (16th December 2016) - Hammann, Jeffrey M.; Lutter, Ferdinand H.; Haas, Diana; Knochel, Paul
Abstract: We report a robust and broadly applicable CoCl2 ‐catalyzed cross‐coupling between functionalized aryl and heteroaryl zinc pivalates and various electron‐poor aryl and heteroaryl halides (X=Cl, Br, I). Couplings with (E)‐ or (Z)‐bromo‐ or iodo‐alkenes proceed with retention of configuration. Also, alkynyl bromides react with arylzinc pivalates providing arylated alkynes.